Investasi dalam Pengembangan Karyawan: Kunci untuk Meningkatkan Kinerja Organisasi: Investing in Individual Employee Development: Key to Improving Organizational Performance - Qurratu'aini, Nafia Ilhama (Universitas Nahdlatul Ulama Sidoarjo, 2024)
In the face of globalization and increasingly intense business competition, improving organizational performance has become a top priority for many companies. One approach that has proven effective in achieving this goal is through investing in employee development programs. This research aims to explore how employee development programs can influence organizational performance, using a literature study approach. The findings from this research show that employee development programs which include competency-based training, mentoring, coaching, and job rotation, have a positive impact in improving employee skills, motivation and loyalty. In addition, evaluations conducted through satisfaction surveys, competency tests, and performance assessments help ensure that the program is continuously improved and adapted to the company's changing needs. The results of this research also confirm that investment in employee development programs is not only able to increase productivity and quality of company operations, but also preparing organizations to face the challenges of technological change and market dynamics in the future.